Maximizing value and minimizing barriers: Patient-centered community consultation for research in emergency settings. (February 2017) - Fordyce, Christopher B; Roe, Matthew T; Dickert, Neal W
Background: Patients with cardiac arrest and other life-threatening emergencies are unable to provide prospective consent for clinical trials. In the United States and other countries, regulations permit an exception from the requirement for informed consent in emergency settings. However, many potential barriers exist, as evidenced by the scarcity of US trials conducted under exception from the requirement for informed consent. One persistent challenge is the requirement that investigators consult communities prior to study approval. Methods: To improve the community consultation process for emergency studies under exception from the requirement for informed consent, we propose that prioritizing engagement of individuals who have experienced the condition under study, or are at high risk for the condition, fulfills regulatory goals and represents the interests of potential enrollees and the community without impeding research. Results: Prioritizing patients engages individuals who are more likely to understand the concerns and experiences of study subjects, to appreciate risks and benefits of the study, and to understand the impact of the disease and intervention on patients' lives than are members of the general public. Similarly, those explicitly at high risk are more likely to identify as potential participants and may impart some level of accountability on the investigator. Finally, the most logical community of relevance is defined by a combination of condition-related experience and living in the area where a study will be conducted; geographic and condition-related communities should not be treated as distinct. In this sense, patients, their family members, and individuals at high risk within the catchment area represent the appropriate "community." Conclusion: Exception from the requirement for informed consent regulations have advanced the goal of improving care for emergency conditions, but common interpretations of the community consultation requirement threaten research in the United States. Focusing on the goals of learning from and demonstrating respect for those most directly affected by a study through engaging people most connected to the condition of interest will make community consultation more valuable, better inform institutional review boards, and increase efficiency.